Individualized 131I-mIBG therapy in the management of refractory and relapsed neuroblastoma. Issue 5 (May 2016) - George, Sally L.; Falzone, Nadia; Chittenden, Sarah; Kirk, Stephanie J.; Lancaster, Donna; Vaidya, Sucheta J.; Mandeville, Henry; Saran, Frank; Pearson, Andrew D.J.; Du, Yong; Meller, Simon T.; Denis-Bacelar, Ana M.; et al.
Abstract : Objective: Iodine-131-labelled meta-iodobenzylguanidine ( 131 I-mIBG) therapy is an established treatment modality for relapsed/refractory neuroblastoma, most frequently administered according to fixed or weight-based criteria. We evaluate response and toxicity following a dosimetry-based, individualized approach. Materials and methods: A review of 44 treatments in 25 patients treated with 131 I-mIBG therapy was performed. Patients received 131 I-mIBG therapy following relapse ( n =9), in refractory disease ( n =12), or with surgically unresectable disease despite conventional treatment ( n =4). Treatment schedule (including mIBG dose and number of administrations) was individualized according to the clinical status of the patient and dosimetry data from either a tracer study or previous administrations. Three-dimensional tumour dosimetry was also performed for eight patients. Results: The mean administered activity was 11089±7222 MBq and the mean whole-body dose for a single administration was 1.79±0.57 Gy. Tumour-absorbed doses varied considerably (3.70±3.37 mGy/MBq). CTCAE grade 3/4 neutropenia was documented following 82% treatments and grade 3/4 thrombocytopenia following 71% treatments. Further acute toxicity was found in 49% of patients. All acute toxicities resolved with appropriate therapy. The overall response rate was 58% (complete or partial response), with a further 29% of patients having stable disease. Conclusion: A highly personalized approach combining patient-specific dosimetry and clinical judgement enables delivery of high activities that can be tolerated by patients, particularly with stem cell support. We report excellent response rates and acceptable toxicity following individualized 131 I-mIBG therapy.